Surgical Outcomes of Ahmed Glaucoma Valve Implantation Without Plate Sutures: A 10-Year Retrospective Study. Issue 6 (June 2021) - Kapelushnik, Noa; Singer, Reut; Barkana, Yaniv; Rosenfeld, Alik; Tucker, Yisrael; Jaber, Wasim; Gaton, Dan; Leshno, Ari; Skaat, Alon
Abstract : Précis: Ahmed glaucoma valve (AGV) implantation without plate fixation resulted in high rates of complications related to plate or tube movement. Purpose: Scleral suturing of the plate of AGV is associated with technical difficulty and potential complications. This study summarizes the surgical outcomes of 10 years of experience with AGV implantation without suture plate fixation. Methods: The medical records of all glaucoma patients who underwent AGV implantation surgery without plate fixation between 2009 and 2019 at the Sheba Medical Center (Tel Hashomer, Israel) were retrospectively reviewed. Clinical data on intraoperative and postoperative complications, best-corrected visual acuity, intraocular pressure, and number of intraocular pressure-lowering medications were retrieved. Results: Included were 95 eyes of 95 patients (53 men, 42 women; mean age, 54.9±17.5 y). The mean follow-up was 687±673 days. In total, 37 patients (37/95, 38.%) had AGV-related complications, of whom 28 (29.5%) required additional intervention. Women had a significantly higher rate of complications than men (21/42, 50% vs. 16/53, 30.2%, respectively, P =0.049). The 2 most common complications were AGV migration in 13 eyes (13.7%) and tube exposure/AGV extrusion in 9 eyes (9.5%). AGV was removed in 10 cases. Conclusions: In this cohort, omitting suture AGV plate fixation resulted in high rates of complications related to plate or tube movement, the need for further intervention, and AGV removal. Therefore, we cannot recommend this surgical technique. Abstract : Supplemental Digital Content is available in the text.